1999
DOI: 10.1002/(sici)1099-0518(19990815)37:16<3317::aid-pola30>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman investigations of PVDF‐based proton‐conducting membranes

Abstract: Proton‐conducting membranes of poly(vinylidene fluoride), PVDF, grafted with styrene and thereafter sulfonated, were investigated by Raman spectroscopy. The depth and surface distribution of polystyrene grafts and crosslinker, as well as the sulfonation efficiency, were determined by using confocal micro‐Raman spectroscopy. Highly grafted samples show homogeneous distribution of grafted material and homogeneous sulfonation. Depth profiles reveal uneven graft distribution for samples with low and intermediate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 24 publications
2
44
1
Order By: Relevance
“…The original PVDF film is very oriented: the processing has left stripes that are visible to the naked eye. Raman spectroscopy has shown that the anisotropy is observable on a microscopic scale 17. The tensile testing demonstrates that the mechanical properties of the original film with and across the machine direction differ considerably.…”
Section: Resultsmentioning
confidence: 98%
“…The original PVDF film is very oriented: the processing has left stripes that are visible to the naked eye. Raman spectroscopy has shown that the anisotropy is observable on a microscopic scale 17. The tensile testing demonstrates that the mechanical properties of the original film with and across the machine direction differ considerably.…”
Section: Resultsmentioning
confidence: 98%
“…The transverse concentration profile was analysed via EDX spectroscopy using a sulfur mapping as graft propagation tracer. To determine the graft distribution several other techniques have also been used, such as vibrational spectroscopy 42,43 or confocal laser scanning microscopy. 44,45 For the sulfur microprobing approach, membranes with GL of 10, 25, 46 and 67% were swollen in water and subsequently broken under liquid nitrogen to obtain a clean wileyonlinelibrary.com/journal/pi cross-section of the membranes.…”
Section: Resultsmentioning
confidence: 99%
“…It should be pointed that since the -and -phase are similar to each other in short segmental conformations the identification of crystal phase between and in FTIR spectrum is still in dispute. On the basis of the data from literature the absorption band at 763 cm -1 is related to In-plane bending or rocking vibration in phase (N. Betz, 1994& S. Lanceros-Me ndez, 2001, the band at 840 cm -1 stretching in or phase (G. Chi Chen, 1994 , V. Bharti, 1997, B. Mattsson, 1999& M. Benz, 2002, the band at 1173 cm −1 is associated to the symmetrical stretching of -CF 2 group (M. Rajendran, 2010). The band at 1234 cm −1 is related to the phase and 1453 cm -1 is assigned to in-plane bending or scissoring of CH 2 group (M. Rajendran, 2010& Garton, 1992).…”
Section: Resultsmentioning
confidence: 99%